A high elastic modulus ultra-durable stc concrete

CN122853786APending Publication Date: 2026-10-02YUNNAN CONSTRUCTION INVESTMENT GREEN DEVELOPMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611098137.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-10-02

AI Technical Summary

Technical Problem

本发明目的在于克服现有STC混凝土弹性模量不足、内部孔隙多、耐久性差、原料易团聚、钢纤维分散不均的缺陷,提供一种高弹性模量超耐久STC混凝土

Benefits of technology

1.本发明用硅烷轻微改性的纳米二氧化硅和2-丙烯酰胺-2-甲基丙磺酸改性的高吸水树脂组成复合材料。通过限定比例,改性的纳米材料能均匀分散在水泥浆体中,填充毛细孔隙,并与水泥水化产物形成化学键合,提高界面过渡区的质量。高吸水树脂在碱性环境下稳定,预吸水后能缓慢释放水分,养护混凝土。这两种材料分别填充孔隙和调控水化,减少基体连通孔隙,提高混凝土的密实度和耐久性。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

This invention relates to the field of concrete preparation technology and discloses a high-elasticity modulus ultra-durable STC concrete, comprising the following raw materials by weight: 100 parts cement, 25-30 parts mineral admixtures, 90-120 parts multi-graded natural sand, 2.5-3.5 parts steel fiber, 1.2-1.5 parts water-reducing agent, 1-2 parts functional materials, and water. The amount of water added is determined by the mass ratio of water to gel material, which is 0.15-0.18. The mass of the gel material is the total mass of cement and mineral admixtures. By improving raw material mixing, multi-grade aggregate matching, two-component material modification, and adding segmented pre-dispersion, superabsorbent resin pre-absorption, step-by-step feeding, and gradient temperature-controlled steam curing processes, the density and interfacial structure of the concrete are improved, giving the concrete high elastic modulus, low porosity, and ultra-durable corrosion resistance. At the same time, the on-site construction batching procedure is simplified, making it suitable for large-scale engineering applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of concrete preparation technology, specifically to a high elastic modulus ultra-durable STC concrete. Background Technology

[0002] Currently, conventional ultra-high toughness concrete (STC) is widely used in engineering scenarios such as steel box girder paving and heavy-duty municipal pavement. Existing commercial STC products generally adopt a production mode of direct dry mixing of nano-powders and undisturbed addition of ordinary water-absorbing resin. In the actual engineering mixing process, unmodified fumed silica is prone to agglomeration and clumping due to molecular hydrogen bonds. When directly added to cement slurry, it cannot be evenly dispersed. Most of the powder agglomerates form local defect points, which not only fail to fill pores and optimize interfaces, but also form fine particles inside the matrix. In weak areas, ordinary polyacrylic acid superabsorbent resins, without monomer modification, rapidly lose their water absorption and retention capacity in the high-alkali, high-calcium ion slurry environment formed by cement hydration. During the mixing stage, they quickly deplete free water, causing the fluidity of the mixture to become uncontrollable. Additional mixing water needs to be added on-site, forcing an increase in the actual water-cement ratio. In the later stages, the resin loses water rapidly, making long-term internal curing impossible. The cementitious material lacks moisture during the later stages of hydration, the matrix is ​​not fully hydrated, and the number of internal capillary pores is excessive. As a result, the durability indicators of the finished product, such as resistance to chloride ion penetration, do not meet the requirements for long-term service of bridge decks. Meanwhile, conventional production lacks pre-dispersion processes for nano-polymers and pre-absorbent polymers. All raw materials are added to the mixer at once, and the simultaneous addition of steel fibers, fine aggregates, and nanoparticles easily leads to clumping and entanglement. After molding, the fiber distribution is uneven, and some areas lack fiber-resistant crack protection, making them prone to developing microcracks under load. Conventional curing often involves uncontrolled direct steam curing or natural curing, with no constraint on the heating rate. The temperature difference between the inside and outside of the concrete generates temperature stress, leading to internal hidden microcracks and further reducing the elastic modulus and long-term durability of the finished product. Conventional STC often uses single-size aggregate, resulting in large aggregate porosity. More cement paste is needed to fill the voids, indirectly increasing the water-cement ratio. With these multiple shortcomings, existing STC, under long-term alternating wet and dry conditions and chloride ion corrosion on 4.5cm thin steel box girder paving, develops surface cracks and internal water seepage after only a few years of service, resulting in high maintenance and repair costs. The industry needs to optimize product performance across the entire chain, from raw material modification and proportion optimization to segmented preparation and gradient curing.

[0003] Based on this, this application provides a high elastic modulus ultra-durable STC concrete. Summary of the Invention

[0004] Technical problems to be solved The purpose of this invention is to overcome the shortcomings of existing STC concrete, such as insufficient elastic modulus, numerous internal pores, poor durability, easy agglomeration of raw materials, and uneven dispersion of steel fibers, and to provide a high elastic modulus and ultra-durable STC concrete.

[0005] Technical solution To achieve the above objectives, the present invention provides the following technical solution: A high-elasticity, ultra-durable STC concrete comprises the following raw materials in parts by weight: 100 parts cement, 25-30 parts mineral admixtures, 90-120 parts multi-graded natural sand, 2.5-3.5 parts steel fiber, 1.2-1.5 parts water-reducing agent, 1-2 parts functional materials, and water; The amount of water added is determined by the ratio of water to gel material mass, which is 0.15-0.18. The mass of the gel material is the total mass of cement and mineral admixtures. The functional materials include silane coupling agent modified nano-silica and modified superabsorbent resin.

[0006] Furthermore, the mineral admixture is obtained by mixing slag powder and silica fume at a mass ratio of (0.8-1.2):1.

[0007] Furthermore, the multi-graded natural sand specifically includes sand 1, sand 2 and sand 3, with a mass ratio of (180-450):(180-220):(350-620).

[0008] Furthermore, the particle size of sand 1 is 20-40 mesh, the particle size of sand 2 is 40-70 mesh, and the particle size of sand 3 is 70-140 mesh.

[0009] Furthermore, the silane coupling agent modified nano-silica is specifically prepared by the following steps: A1. At room temperature, add glacial acetic acid to deionized water and silane coupling agent, stir for 3-5 minutes, then add anhydrous ethanol, and stir at 200-300 rpm for 25-30 minutes to hydrolyze and obtain hydrolyzed silane. A2. Mix nano-silica in a mixer at a rate of 800-900 rpm, and spray the hydrolyzed silane solution at a constant speed and atomize it at room temperature for 12-15 minutes. After spraying, keep it at 50±2℃ and stir for 60-90 minutes to obtain the modified powder. A3. Dry the modified powder at 50-60℃ for 5-6 hours, then pass it through a 150-mesh sieve to obtain silane coupling agent modified nano-silica.

[0010] Furthermore, the mass ratio of nano-silica, silane coupling agent, anhydrous ethanol, deionized water and glacial acetic acid is 100: (1.8-2.2): (8-12): (5-7): (0.08-0.12).

[0011] In the above preparation method, the silane coupling agent modifies the nano-silica by treating the silica surface with the coupling agent, transforming the hydrophilic hydroxyl groups into hydrophobic organic functional groups. By controlling the reaction conditions, the modification cost is reduced, while preventing the modified nano-silica from becoming excessively hydrophobic and affecting the subsequent pozzolanic reaction. This modification method significantly disrupts hydrogen bond aggregation, improving the dispersion stability of nano-silica in cement slurry. Furthermore, the modified silica can form a certain degree of interfacial bonding with cement hydration products, improving the interfacial transition zone. In addition, compared to the process of preparing a modified sol, it eliminates the need for on-site pre-dispersion, alcoholysis, and ultrasonication, facilitating on-site batching in engineering projects.

[0012] Furthermore, the modified superabsorbent resin is specifically prepared by the following steps: Acrylic acid was added to a reactor, and the temperature was controlled by an ice-water bath. NaOH solid was added in batches, and the mixture was stirred and neutralized until the pH of the system reached 6.0-6.5. Then 2-acrylamido-2-methylpropanesulfonic acid and acrylamide were added and stirred until dissolved. Crosslinking agent and initiator were added in sequence, and stirring was continued until dissolved. The system temperature was then raised to 50-55℃ and allowed to stand for polymerization for 3.5-4 hours. The resulting gel system was cut into 3-5mm particles and dried with hot air at 80-90℃ until the moisture content was ≤6%, thus obtaining the modified superabsorbent resin.

[0013] Furthermore, the crosslinking agent is N,N-methylenebisacrylamide, and the initiator is ammonium persulfate.

[0014] Further, the mass ratio of acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, acrylamide, deionized water, solid NaOH, crosslinking agent and initiator is 100:(18-22):(8-12):220:(48-52):(0.06-0.09):(0.35-0.45).

[0015] In the above technical solution, the introduction of sulfonic acid groups through 2-acrylamide-2-methylpropanesulfonic acid increases the negative charge density of the resin network, significantly improving the high alkali and high Ca content of cement. 2+ It has good water retention stability in the environment and will not lose water quickly in the mortar.

[0016] A high-elasticity modulus ultra-durable STC concrete, the preparation method of which specifically includes the following steps: S1. Take the modified superabsorbent resin of the formula, add water of the formula amount, soak and stand at room temperature for 5-10 minutes to prepare superabsorbent resin gel particles. S2. Modified nano-silica pre-mixed slurry: Weigh out the silane coupling agent modified nano-silica, water-reducing agent and water according to the formula, put them into a high-speed disperser, control the speed at 2000-3000 rpm, and stir continuously for 5-10 minutes to obtain the pre-dispersed slurry. S3. Add all the cement, mineral admixtures and multi-graded natural sand in the formula to the planetary mixer and dry mix at room temperature for 2-3 minutes. Then add the pre-dispersed slurry prepared in S1 and the remaining water after deducting the water used in S1 and S2, and continue mixing for 2-3 minutes to obtain cement mortar. S4. Add the superabsorbent resin gel particles prepared in S2 to the above cement mortar and stir at a speed of 40-80 rpm for 1-2 min; add the steel fiber into the mixer in three batches, and stir at a speed of 120-180 rpm after each batch of material is added, and stir for a total of 3-5 min. S5. Immediately after mixing and discharging, the material is spread and leveled using an XD-CZP laser ultrasonic screed. The paving thickness error is controlled to 0 to +3 mm by automatic elevation control of the equipment. After paving, the material is simultaneously covered with a film for moisture retention and allowed to stand still at room temperature for 4-6 hours. The moisture retention film curing time is ≥24 hours. Subsequently, a sealed steam curing shed is erected, with steam supplied by a boiler. The heating rate is ≤12℃ / h, and the temperature is uniformly raised to 80℃ for 48-72 hours. After that, the temperature is slowly lowered to room temperature at a rate ≤15℃ / h. The humidity in the steam curing chamber is ≥95% throughout the process, thus obtaining high elastic modulus ultra-durable STC concrete.

[0017] Beneficial technical effects 1. This invention uses a composite material composed of slightly modified silane nano-silica and 2-acrylamide-2-methylpropanesulfonic acid-modified superabsorbent resin. By limiting the proportions, the modified nanomaterials can be uniformly dispersed in cement paste, filling capillary pores and forming chemical bonds with cement hydration products, thus improving the quality of the interfacial transition zone. The superabsorbent resin is stable in an alkaline environment and can slowly release water after pre-absorbing water, thus curing the concrete. These two materials respectively fill pores and regulate hydration, reducing interconnected pores in the matrix and improving the density and durability of the concrete.

[0018] 2. In this technical solution, a limited proportion of slag powder and silica fume is used in combination with three-stage natural sand to achieve dense particle packing and reduce the porosity of the slurry. Steel fibers are added in stages to prevent fiber agglomeration, ensuring a random distribution within the matrix and forming a three-dimensional crack-resistant skeleton that macroscopically constrains crack propagation. The micro-aggregates and modified fillers form a multi-level dense structure, improving the material's elastic modulus and mechanical stability.

[0019] 3. In terms of the preparation process, pretreatment avoids the problems of nano-agglomeration, early water competition from superabsorbent resin, and steel fiber clumping. Pre-dispersion uses a water-reducing agent to stabilize the nanoparticles, pre-absorption isolates the superabsorbent resin from competition with the mixing water, and gradient temperature steam curing avoids internal micro-cracks and promotes complete hydration reaction. The entire process is compatible with existing engineering mixing and steam curing equipment, requiring no additional special processing equipment, and is suitable for large-scale on-site construction and production.

[0020] 4. Through raw material blending and process optimization, the product achieves a balance between the construction performance of fresh concrete and the mechanical durability of hardened concrete in an ultra-low water-cement ratio system. Compared to conventional unmodified STC products, it offers systematic improvements in resistance to ion penetration, environmental erosion, and load deformation control, making it suitable for long-term alternating load applications such as steel box girder bridge decks and heavy-duty pavements. All components utilize industrially produced raw materials, minimizing the difficulty of raw material procurement and mass production implementation. Detailed Implementation

[0021] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0022] The raw materials used in the embodiments and comparative examples of this invention are shown in Table 1 below.

[0023] Table 1 ; In the following examples and comparative examples, the silane coupling agent-modified nano-silica and the modified superabsorbent resin were prepared using a general technical method. The general preparation method for silane coupling agent-modified nano-silica is as follows: A1. At room temperature, add glacial acetic acid to deionized water and silane coupling agent, stir for 3-5 minutes, then add anhydrous ethanol, and stir at 200-300 rpm for 25-30 minutes to hydrolyze and obtain hydrolyzed silane. A2. Mix nano-silica in a mixer at a rate of 800-900 rpm, and spray the hydrolyzed silane solution at a constant speed and atomize it at room temperature for 12-15 minutes. After spraying, keep it at 50±2℃ and stir for 60-90 minutes to obtain the modified powder. A3. Dry the modified powder at 50-60℃ for 5-6 hours, then pass it through a 150-mesh sieve to obtain silane coupling agent modified nano-silica.

[0024] The general preparation method for modified superabsorbent resin is as follows: Acrylic acid was added to a reaction vessel, and the temperature was controlled in an ice-water bath. NaOH solid was added in batches, and the mixture was stirred and neutralized until the pH of the system reached 6.0-6.5. Then, 2-acrylamido-2-methylpropanesulfonic acid and acrylamide were added and stirred until dissolved. After that, the crosslinking agent and initiator were added in sequence and stirred until dissolved. The system temperature was then raised to 50-55℃ and allowed to stand for polymerization for 3.5-4 hours. The resulting gel system was cut into 3-5mm particles and dried with hot air at 80-90℃ until the moisture content was ≤6%, thus obtaining the modified superabsorbent resin. The crosslinking agent used was N,N-methylenebisacrylamide, and the initiator was ammonium persulfate.

[0025] The mixing equipment used in the following examples and comparative examples is a DMP1500 vertical shaft planetary mixer; the leveling equipment is an XD-CZP ultrasonic laser leveler; the steam curing equipment is an LSH2.1-0.8-S type steam boiler; and the transfer equipment is a small dump truck.

[0026] Example 1 A high-elasticity, ultra-durable STC concrete specifically comprises the following raw materials in parts by weight: 100 parts cement, 27 parts mineral admixture (slag powder: silica fume = 1:1), 105 parts multi-grade natural sand (sand 1: sand 2: sand 3 = 315:200:485, sand 1 particle size 20-40 mesh, sand 2 particle size 40-70 mesh, sand 3 particle size 70-140 mesh), 3.0 parts steel fiber, 1.35 parts water-reducing agent, 1.5 parts functional materials (silane coupling agent modified nano silica 0.75 parts, modified superabsorbent resin 0.75 parts), total cementitious material mass 127 parts, water-cement ratio 0.16, total water added for mixing 20.32 parts, of which 22% (4.47 parts) is used for pre-absorption of water by modified superabsorbent resin in S1, and the remaining 15.85 parts are used for S2 and S3 processes; The specific parameters for preparing silane coupling agent modified nano-silica are as follows: 100 parts nano-silica, 2.0 parts silane coupling agent, 10 parts anhydrous ethanol, 6 parts deionized water, 0.10 parts glacial acetic acid, A1 stirring hydrolysis time 28 min, stirring speed 250 rpm, A2 spraying time 13 min, heat preservation reaction 75 min, A3 drying temperature 55℃, drying time 5.5 h; The specific parameters for preparing the modified superabsorbent resin are as follows: 100 parts acrylic acid, 20 parts 2-acrylamide-2-methylpropanesulfonic acid, 10 parts acrylamide, 220 parts deionized water, 50 parts NaOH, 0.075 parts N,N-methylenebisacrylamide, 0.40 parts ammonium persulfate, pH 6.2 neutralized with B1, polymerization temperature 52℃, polymerization time 3.75h, gel pellets 4mm, and drying temperature 85℃. A method for preparing high elastic modulus ultra-durable STC concrete specifically includes the following steps: S1. Take 0.75 parts of modified superabsorbent resin and add 4.47 parts of water to soak at room temperature for 7 minutes to obtain superabsorbent resin gel; S2. Take 0.75 parts of modified nano silica, 1.35 parts of water-reducing agent, and 15.85 parts of remaining water and put them into a high-speed disperser at 2500 rpm for 7.5 min to make a pre-dispersed slurry; S3. Add all dry materials to a planetary mixer and dry mix at room temperature for 2.5 minutes. Add pre-dispersed slurry and continue mixing for 2.5 minutes to obtain cement mortar. S4. Add superabsorbent resin gel particles and stir at 60 rpm for 1.5 min. Add steel fibers in 3 batches, stirring at 150 rpm after each batch, for a total of 4 min of stirring. S5. The discharged material is leveled by an XD-CZP laser ultrasonic screed, left to stand at room temperature for 5 hours, covered with film for 24 hours, heated in a sealed steam curing shed at a rate of 10℃ / h to 80℃ and kept at that temperature for 60 hours, then cooled down to room temperature at a rate of 12℃ / h, with the humidity inside the shed maintained at 96%, thus producing high elastic modulus ultra-durable STC concrete.

[0027] Example 2 A high-elasticity, ultra-durable STC concrete specifically comprises the following raw materials in parts by weight: 100 parts cement, 25 parts mineral admixture (slag powder: silica fume = 0.9:1), 95 parts multi-grade natural sand (sand 1: sand 2: sand 3 = 225:190:395, sand 1 particle size 20-40 mesh, sand 2 particle size 40-70 mesh, sand 3 particle size 70-140 mesh), 2.5 parts steel fiber, 1.2 parts water-reducing agent, 1.0 part functional material (silane coupling agent modified nano silica 0.5 parts, modified superabsorbent resin 0.5 parts), total mass of cementitious materials 125 parts, water-cement ratio 0.15, total water added for mixing 18.75 parts, S1 pre-absorption water accounts for 20% of the total water, i.e. 3.75 parts, the remaining 15 parts are used for S2 and S3 processes; The specific parameters for preparing silane coupling agent modified nano-silica are as follows: 100 parts nano-silica, 1.8 parts silane coupling agent, 8 parts anhydrous ethanol, 5 parts deionized water, 0.08 parts glacial acetic acid, A1 stirring hydrolysis time 25 min, stirring speed 200 rpm, A2 spraying time 12 min, heat preservation reaction 60 min, A3 drying temperature 50℃, drying time 5 h. The specific parameters for preparing the modified superabsorbent resin are as follows: 100 parts acrylic acid, 18 parts 2-acrylamide-2-methylpropanesulfonic acid, 8 parts acrylamide, 220 parts deionized water, 48 parts NaOH, 0.06 parts N,N-methylenebisacrylamide, 0.35 parts ammonium persulfate, pH 6.0 neutralized with B1, polymerization temperature 50℃, polymerization time 3.5h, gel pellets 3mm, and drying temperature 80℃. A method for preparing high elastic modulus ultra-durable STC concrete specifically includes the following steps: S1. Take 0.5 parts of modified superabsorbent resin and add 3.75 parts of water to soak at room temperature for 5 minutes to obtain superabsorbent resin gel; S2. Take 0.5 parts of modified nano silica, 1.2 parts of water-reducing agent, and 15 parts of remaining water and put them into a high-speed disperser and stir at 2000 rpm for 5 minutes to prepare a pre-dispersed slurry. S3. Add all dry materials to the planetary mixer and dry mix at room temperature for 2 minutes. Add the pre-dispersed slurry and continue mixing for 2 minutes to obtain cement mortar. S4. Add superabsorbent resin gel particles and stir at 40 rpm for 1 min. Add steel fiber in 3 batches, stirring at 120 rpm after each batch, and stir for a total of 3 min. S5. The material is leveled by an XD-CZP laser ultrasonic screed, left to stand at room temperature for 4 hours, covered with film for 24 hours, heated to 80℃ in a sealed steam curing shed at a rate of 11℃ / h and kept at that temperature for 48 hours, then cooled to room temperature at a rate of 13℃ / h, with the humidity inside the shed maintained at 96%, to produce high elastic modulus ultra-durable STC concrete.

[0028] Example 3 A high-elasticity, ultra-durable STC concrete specifically comprises the following raw materials in parts by weight: 100 parts cement, 30 parts mineral admixture (slag powder: silica fume = 1.2:1), 118 parts multi-grade natural sand (sand 1: sand 2: sand 3 = 420:215:595, sand 1 particle size 20-40 mesh, sand 2 particle size 40-70 mesh, sand 3 particle size 70-140 mesh), 3.5 parts steel fiber, 1.5 parts water-reducing agent, 2.0 parts functional materials (silane coupling agent modified nano silica 1.0 part, modified superabsorbent resin 1.0 part), total mass of cementitious materials 130 parts, water-cement ratio 0.18, total water added for mixing 23.4 parts, water used for S1 pre-absorption accounts for 24% of the total water used, i.e. 5.62 parts, the remaining 17.78 parts are used for S2 and S3 processes; The specific parameters for preparing silane coupling agent modified nano-silica are as follows: 100 parts of nano-silica, 2.2 parts of silane coupling agent, 12 parts of anhydrous ethanol, 7 parts of deionized water, 0.12 parts of glacial acetic acid; A1 stirring and hydrolysis time 30 min, stirring speed 300 rpm; A2 spraying time 15 min, heat preservation reaction 90 min; A3 drying temperature 60℃, drying time 6 h. The specific parameters for preparing the modified superabsorbent resin are as follows: 100 parts acrylic acid, 22 parts 2-acrylamide-2-methylpropanesulfonic acid, 12 parts acrylamide, 220 parts deionized water, 52 parts NaOH, 0.09 parts N,N-methylenebisacrylamide, 0.45 parts ammonium persulfate, pH 6.5 neutralized with B1, polymerization temperature 55℃, polymerization time 4h, gel pellets 5mm, and drying temperature 90℃. A method for preparing high elastic modulus ultra-durable STC concrete specifically includes the following steps: S1. Take 1.0 part of modified superabsorbent resin and add 5.62 parts of water to soak at room temperature for 10 minutes to obtain superabsorbent resin gel; S2. Take 1.0 part of modified nano silica, 1.5 parts of water-reducing agent, and 17.78 parts of remaining water and put them into a high-speed disperser at 3000 rpm for 10 min to prepare a pre-dispersed slurry; S3. Add all dry materials to the planetary mixer and dry mix at room temperature for 3 minutes. Add the pre-dispersed slurry and continue mixing for 3 minutes to obtain cement mortar. S4. Add super absorbent resin gel particles and stir at 80 rpm for 2 minutes. Add steel fiber in 3 batches, stirring at 180 rpm after each batch. Stir for a total of 5 minutes. S5. The discharged material is leveled by an XD-CZP laser ultrasonic screed, left to stand at room temperature for 6 hours, covered with film for 25 hours, heated to 80℃ in a sealed steam curing shed at a rate of 12℃ / h and kept at that temperature for 72 hours, then cooled to room temperature at a rate of 15℃ / h, with the humidity inside the shed maintained at 96%, thus producing high elastic modulus ultra-durable STC concrete.

[0029] Example 4 The difference between this embodiment and Embodiment 1 is that the raw materials in this embodiment are proportioned by weight as follows: 100 parts cement, 25 parts mineral admixture (slag powder: silica fume = 1:1, 12.5 parts slag powder, 12.5 parts silica fume), and 101 parts multi-graded natural sand (sand 1: sand 2: sand 3 = 433:192:385, sand 1 particle size 20-40 mesh, sand 2 particle size 40-70 mesh, sand 3 particle size 70-140 mesh). The mixture consists of 2.5 parts steel fiber, 1.85 parts water-reducing agent, and 1.5 parts functional materials (0.75 parts silane coupling agent modified nano-silica and 0.75 parts modified superabsorbent resin). The total mass of the cementitious material is 125 parts, the water-cement ratio is 0.17, and the total water added during mixing is 21.25 parts. Among them, the water used for pre-absorbing water of S1 modified superabsorbent resin accounts for 22% of the total water, i.e., 4.68 parts, and the remaining 16.57 parts are used for S2 and S3 processes.

[0030] Example 5 The difference between this embodiment and Embodiment 1 is that the raw materials in this embodiment are proportioned by weight as follows: 100 parts cement, 25 parts mineral admixture (slag powder: silica fume = 1:1, 12.5 parts slag powder, 12.5 parts silica fume), and 101 parts multi-graded natural sand (sand 1: sand 2: sand 3 = 433:192:385, sand 1 particle size 20-40 mesh, sand 2 particle size 40-70 mesh, sand 3 particle size 7... The mixture consists of 0-140 mesh steel fiber, 2.5 parts water-reducing agent, 2.0 parts functional material (0.75 parts silane coupling agent modified nano silica, 0.75 parts modified superabsorbent resin), 125 parts cementitious material, a water-cement ratio of 0.17, 21.25 parts water added during mixing, 4.68 parts of the S1 pre-absorption water account for 22% of the total water, and the remaining 16.57 parts are used for S2 and S3 processes.

[0031] Example 6 The difference between this embodiment and Embodiment 1 is that the raw materials in this embodiment are proportioned by weight as follows: 100 parts cement, 24 parts mineral admixture (slag powder: silica fume ≈ 0.97:1, 11.8 parts slag powder, 12.2 parts silica fume), and 101 parts multi-graded natural sand (sand 1: sand 2: sand 3 = 433:192:385, sand 1 particle size 20-40 mesh, sand 2 particle size 40-70 mesh, sand 3 particle size...). The mixture consists of 70-140 mesh diameter steel fiber, 2.5 parts water-reducing agent, 2.0 parts functional material (0.75 parts silane coupling agent modified nano-silica, 0.75 parts modified superabsorbent resin), total cementitious material mass 124 parts, water-cement ratio 0.17, total water added during mixing 21.08 parts, S1 pre-absorption water accounts for 22% of the total water, i.e. 4.64 parts, and the remaining 16.44 parts are used for S2 and S3 processes.

[0032] Example 7 The difference between this embodiment and Embodiment 1 is that the raw materials in this embodiment are proportioned by weight as follows: 100 parts cement, 24 parts mineral admixture (slag powder: silica fume = 0.97:1, 11.8 parts slag powder, 12.2 parts silica fume), and 101 parts multi-graded natural sand (sand 1: sand 2: sand 3 = 433:192:385, sand 1 particle size 20-40 mesh, sand 2 particle size 40-70 mesh, sand 3 particle size 70-1...). The mixture consists of 40 mesh steel fiber, 3.0 parts water-reducing agent, 2.0 parts water-reducing agent, and 1.5 parts functional materials (0.75 parts silane coupling agent modified nano-silica and 0.75 parts modified superabsorbent resin). The total mass of the cementitious material is 124 parts, the water-cement ratio is 0.17, and the total water added during mixing is 21.08 parts. Among them, the water used for pre-absorbing water of the modified superabsorbent resin in S1 accounts for 22% of the total water, i.e., 4.64 parts, and the remaining 16.44 parts are used for processes S2 and S3.

[0033] Example 8 The difference between this embodiment and Embodiment 1 is that the raw materials in this embodiment are proportioned by weight as follows: 90 parts cement, 24 parts mineral admixture (slag powder: silica fume = 0.97:1, 11.8 parts slag powder, 12.2 parts silica fume), and 101 parts multi-graded natural sand (sand 1: sand 2: sand 3 = 433:192:385, sand 1 particle size 20-40 mesh, sand 2 particle size 40-70 mesh, sand 3 particle size...). The mixture consists of 70-140 mesh steel fiber, 3.0 parts water-reducing agent, 2.3 parts functional materials (0.75 parts silane coupling agent modified nano-silica and 0.75 parts modified superabsorbent resin), with a total cementitious material mass of 114 parts, a water-cement ratio of 0.15, a total water added during mixing of 17.10 parts, 22% of the total water used for S1 pre-absorption (3.76 parts), and the remaining 13.34 parts used for S2 and S3 processes.

[0034] Comparative Example 1 The difference between this comparative example and Example 1 is that the functional materials and related steps are omitted. Specifically, silane coupling agent-modified nano-silica and modified superabsorbent resin are not added to the formulation. The total amount of water used for mixing is adjusted to 20.32 parts, and the S1 pre-absorption step is omitted, with all water used in steps S2 and S3. Other aspects, such as the dry material ratio, steel fiber, and water-reducing agent, are the same as in Example 1. The preparation method omits S1 and S2; after mixing the dry materials, all the mixing water is added directly, and subsequent mixing and curing steps remain unchanged.

[0035] Comparative Example 2 The difference between this comparative example and Example 1 is that the silane coupling agent-modified nano-silica in Example 1 is replaced with an equal mass of commercially available unmodified hydrophilic nano-silica (HF200 fumed SiO2, particle size 20nm). The addition and pretreatment of the superabsorbent resin remain unchanged. Step S2 is changed to: taking 0.75 parts of unmodified nano-silica, 1.35 parts of water-reducing agent, and 15.85 parts of remaining water and adding them to a high-speed disperser at 2500 rpm for 7.5 min to prepare a pre-dispersed slurry. The remaining steps are the same as in Example 1.

[0036] Comparative Example 3 The difference between this comparative example and Example 1 is that the modified superabsorbent polymer in Example 1 is replaced with an equal mass of commercially available ordinary polyacrylic acid superabsorbent polymer (Yanxing Chemical, YX-30 building material grade SAP). The addition of nano-silica and pretreatment remain unchanged. Step S1: Take 0.75 parts of ordinary superabsorbent polymer and add 4.47 parts of water to soak at room temperature for 7.5 min to obtain superabsorbent polymer gel. Subsequent steps are exactly the same as in Example 1.

[0037] Comparative Example 4 The difference between this comparative example and Example 1 is that the total amount of functional materials is adjusted to 3.0 parts, of which 2.25 parts are silane coupling agent-modified nano-silica and 0.75 parts are modified superabsorbent resin. The amounts in step S2 are adjusted accordingly; specifically, 2.25 parts of modified nano-silica, 1.35 parts of water-reducing agent, and 15.85 parts of remaining water are pre-dispersed in step S2. The rest is the same as in Example 1.

[0038] Comparative Example 5 The difference between this comparative example and Example 1 lies in the preparation parameters of the silane coupling agent modified nano-silica in the functional material. The dosage of silane coupling agent KH550 is increased to 8.0% of the mass of nano-silica, while other preparation parameters remain unchanged. During concrete preparation, it is added after pre-dispersing with water-reducing agent and water according to the dosage and steps of Example 1. The remaining steps are exactly the same as in Example 1.

[0039] The performance of the samples prepared in the examples and comparative examples is now being tested. The specific test methods are as follows: 1. Spreadability Test: Refer to the "Technical Specification for Application of Self-Compacting Concrete" (JGJ / T 283-2012). Load the STC mixture from the mixer into a standard truncated cone cylinder (Φ100mm×Φ200mm×300mm), lift it vertically, and wait for the mixture to stop flowing. Measure the spread diameter in two vertical directions and take the average value.

[0040] The specific test results are shown in Table 2 below.

[0041] Table 2 ; The comparison of the test results in Table 2 shows that the workability of the comparative mixtures after removing all functional materials changed. The nano-components and modified superabsorbent resin in the functional materials synergistically regulate the rheological properties of the slurry from two dimensions: powder dispersion and system water retention. Unmodified nano-silica, due to its native hydrogen bond aggregation, cannot form a stable dispersion system with the water-reducing agent, leading to an increase in flocculated structures within the slurry and thus affecting its flowability. Ordinary superabsorbent resin has insufficient water absorption stability in the high-alkali environment of cement, and during the mixing stage, it grabs water, destroying the original water film structure of the slurry, thus altering the expansion index. Excessive addition of modified nanomaterials will crowd out the free water space of the slurry, disrupting the original particle accumulation and water film balance. The two-component functional material of this invention, with its limited dosage range, relies on two pre-dispersion and pre-absorption processes. On the one hand, it relies on the filling and dispersion of modified nanomaterials in the slurry to optimize the flocculation state of cement particles; on the other hand, it relies on the delayed release of water by modified superabsorbent resin to maintain the stability of free water during the mixing stage. The synergy of these two processes ensures that the expansion of each group of samples remains stable within the specified range. The absence of a single component, the lack of modification of raw materials, and the deviation of component dosage from the optimal range will all disrupt the synergistic relationship between the two control pathways, ultimately resulting in a shift in the extended index.

[0042] 2. Compressive strength test: Refer to the "Test Procedures for Cement and Cement Concrete in Highway Engineering" (JTG 3420-2020). Mold 100mm×100mm×100mm cubic specimens and steam-cur them under the same conditions as the structural members (heating at 10℃ / h to 80℃, holding at that temperature for 60h, then cooling at 12℃ / h). Then, use a pressure testing machine (loading rate 1.2MPa / s) to test their failure load and calculate the compressive strength.

[0043] 3. Flexural strength test: Refer to the "Test Procedures for Cement and Cement Concrete in Highway Engineering" (JTG 3420-2020). Mold 100mm×100mm×400mm prism specimens, steam-cured under the same conditions, and then tested for flexural strength using a four-point bending loading method (span 300mm, loading rate 0.08MPa / s).

[0044] 4. Elastic modulus test: Refer to the "Test Procedures for Cement and Cement Concrete in Highway Engineering" (JTG 3420-2020). Mold cylindrical specimens of Φ150mm×300mm, steam-cured under the same conditions, and then fitted with a deformation measuring instrument. The static compressive elastic modulus is determined using the cyclic loading method (with 40% of the axial compressive strength as the upper limit stress).

[0045] The specific test results are shown in Table 3 below.

[0046] Table 3 ; As shown in Table 3, the mechanical test results of each embodiment and comparative example reveal that the two-component functional materials form a microscopic synergistic reinforcement system. Silane-modified nano-silica fills the micron-level capillaries inside the cement matrix, forming interfacial bonds with hydration products to optimize the aggregate-slurry interface and reduce the generation of microscopic defects. 2-Acrylamide-2-methylpropanesulfonic acid-modified superabsorbent resin promotes the continuous hydration of the cementitious material through slow water release in the later stages, increasing the density of the hydration products. Simply removing the functional materials would simultaneously lack both pore filling and long-term internal curing pathways, making it impossible to effectively fill defects inside the matrix. Unmodified nanoparticles, after agglomeration, cannot uniformly fill the pores, thus hindering interfacial reinforcement. With a significant decrease in water content, ordinary superabsorbent resins cannot provide long-term hydration water due to rapid water loss in the early stages, resulting in a decrease in hydration sufficiency. After replacing a single functional raw material, only a single reinforcement path is retained, which cannot achieve a two-way synergistic improvement in micro-density and long-term hydration. Excessive content of functional materials will introduce excess organic components that interfere with the density of the matrix. This invention, under a limited ratio, combines two functional materials with multi-grade aggregates and steel fibers to achieve macroscopic toughening. It synergistically improves compressive strength, flexural strength, and elastic modulus through a three-layer structure of micro-pore optimization, hydration control, and macro-fiber crack resistance. The replacement or removal of any key component will disrupt the three-layer synergistic reinforcement logic, causing an overall decline in mechanical properties.

[0047] 5. Chloride ion migration coefficient test: Refer to the "Rapid Chloride Ion Migration Coefficient Method (RCM Method)" in the "Standard for Test Methods of Long-Term Performance and Durability of Ordinary Concrete" (GB / T 50082-2019). Mold cylindrical specimens of Φ100mm×50mm, steam-cured under the same conditions, and then conduct the RCM test to calculate the chloride ion migration coefficient (D_RCM) and evaluate the resistance to chloride ion penetration.

[0048] The specific test results are shown in Table 4 below.

[0049] Table 4 ; Chloride ion permeation channels primarily rely on interconnected capillary pores within concrete. Data comparisons clearly show that modified nano-silica fills these interconnected pores and refines pore size distribution, blocking the diffusion pathways of chloride ions. Modified superabsorbent polymer (SAP) provides long-term internal curing, improving hydration density and further reducing the formation of harmful interconnected pores. The two work synergistically to reduce chloride ion migration rates from both pore structure and hydration levels. Samples without functional materials exhibit a high number of interconnected pores and abundant chloride ion permeation channels; unmodified nanomaterials, after aggregation, have insufficient filling efficiency, and ordinary SAP internal curing fails, failing to optimize the pore structure in the later stages. Replacing a single raw material only achieves pore optimization along a single path and cannot create a bidirectional sealing effect. Excessive component content introduces new micropores within the matrix, increasing chloride ion migration capacity. The raw material ratio and pretreatment process of this invention achieve synergistic protection from the two functional materials, fundamentally reducing the proportion of harmful pores and lowering the chloride ion migration coefficient. The absence of any key technical element will disrupt the pore sealing synergistic mechanism, leading to a simultaneous decline in impermeability and durability.

[0050] It should be noted that, in this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitation, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.

[0051] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

[0052] Those skilled in the art should understand that the above descriptions are merely several specific embodiments of the present invention, and not all embodiments.

Claims

1. A high-elasticity modulus, ultra-durable STC concrete, characterized in that, Includes the following quantities of raw materials: 100 parts cement, 25-30 parts mineral admixtures, 90-120 parts multi-graded natural sand, 2.5-3.5 parts steel fiber, 1.2-1.5 parts water-reducing agent, 1-2 parts functional materials, and water; The amount of water added is determined by the ratio of water to gel material mass, which is 0.15-0.

18. The mass of the gel material is the total mass of cement and mineral admixtures. The functional materials include silane coupling agent modified nano-silica and modified superabsorbent resin.

2. The high elastic modulus ultra-durable STC concrete according to claim 1, characterized in that, The mineral admixture is obtained by mixing slag powder and silica fume at a mass ratio of (0.8-1.2):

1.

3. The high elastic modulus ultra-durable STC concrete according to claim 1, characterized in that, The multi-graded natural sand specifically includes sand 1, sand 2 and sand 3, with a mass ratio of (180-450):(180-220):(350-620).

4. The high elastic modulus ultra-durable STC concrete according to claim 3, characterized in that, The particle size of sand 1 is 20-40 mesh, the particle size of sand 2 is 40-70 mesh, and the particle size of sand 3 is 70-140 mesh.

5. The high elastic modulus ultra-durable STC concrete according to claim 1, characterized in that, The silane coupling agent modified nano-silica is prepared by the following steps: A1. At room temperature, add glacial acetic acid to deionized water and silane coupling agent, stir for 3-5 minutes, then add anhydrous ethanol, and stir at 200-300 rpm for 25-30 minutes to hydrolyze and obtain hydrolyzed silane. A2. Mix nano-silica in a mixer at a rate of 800-900 rpm, and spray the hydrolyzed silane solution at a constant speed and atomize it at room temperature for 12-15 minutes. After spraying, keep it at 50±2℃ and stir for 60-90 minutes to obtain the modified powder. A3. Dry the modified powder at 50-60℃ for 5-6 hours, then pass it through a 150-mesh sieve to obtain silane coupling agent modified nano-silica.

6. The high elastic modulus ultra-durable STC concrete according to claim 5, characterized in that, The mass ratio of nano-silica, silane coupling agent, anhydrous ethanol, deionized water and glacial acetic acid is 100: (1.8-2.2): (8-12): (5-7): (0.08-0.12).

7. The high elastic modulus ultra-durable STC concrete according to claim 1, characterized in that, The modified superabsorbent resin is prepared by the following steps: Acrylic acid was added to a reaction vessel, and the temperature was controlled in an ice-water bath. NaOH solid was added in batches, and the mixture was stirred and neutralized until the pH of the system reached 6.0-6.

5. Then 2-acrylamido-2-methylpropanesulfonic acid and acrylamide were added and stirred until dissolved. After that, crosslinking agent and initiator were added in sequence and stirred until dissolved. The system temperature was then raised to 50-55℃ and allowed to stand for polymerization for 3.5-4 hours. The resulting gel system was cut into 3-5mm particles and dried with hot air at 80-90℃ until the moisture content was ≤6%, thus obtaining the modified superabsorbent resin.

8. The high elastic modulus ultra-durable STC concrete according to claim 7, characterized in that, The crosslinking agent is N,N-methylenebisacrylamide, and the initiator is ammonium persulfate.

9. The high elastic modulus ultra-durable STC concrete according to claim 8, characterized in that, The mass ratio of acrylic acid, 2-acrylamide-2-methylpropanesulfonic acid, acrylamide, deionized water, solid NaOH, crosslinking agent and initiator is 100:(18-22):(8-12):220:(48-52):(0.06-0.09):(0.35-0.45).

10. The high elastic modulus ultra-durable STC concrete according to claim 1, characterized in that, Its preparation method specifically includes the following steps: S1. Take the modified superabsorbent resin of the formula, add water of the formula amount, soak and stand at room temperature for 5-10 minutes to prepare superabsorbent resin gel particles. S2. Modified nano-silica pre-mixed slurry: Weigh out the silane coupling agent modified nano-silica, water-reducing agent and water according to the formula, put them into a high-speed disperser, control the speed at 2000-3000 rpm, and stir continuously for 5-10 minutes to obtain the pre-dispersed slurry. S3. Add all the cement, mineral admixtures, and multi-graded natural sand to the planetary mixer and dry mix at room temperature for 2-3 minutes. Then add the pre-dispersed slurry and the remaining water after deducting the water used in S1 and S2, and continue mixing for 2-3 minutes to obtain cement mortar. S4. Add the superabsorbent resin gel particles prepared in S2 to the above cement mortar and stir at a speed of 40-80 rpm for 1-2 minutes. Add the steel fibers to the mixer in batches and stir at a speed of 120-180 rpm after each batch is added. Stir for a total of 3-5 minutes. S5. Immediately after mixing and discharging, the material is spread and leveled using an XD-CZP laser ultrasonic screed. After spreading, the material is simultaneously covered with a film to retain moisture. The mixture is then left to stand still at room temperature. Subsequently, a sealed steam curing shed is erected, and steam is supplied from a boiler. The temperature is raised to 70-80℃ at a uniform rate and maintained for 48-72 hours. After that, the temperature is slowly lowered to room temperature to obtain high elastic modulus ultra-durable STC concrete.